THE ROLE OF LOCAL CULTURE IN ENGLISH SPEAKING CLASSES - Saraswati, Girindra; Hartoyo, Hartoyo; Fadwati, Amida (LLT Journal: A Journal on Language and Language Teaching, 2018)
This paper aims at finding out a model or a concrete picture of the role of local culture in intercultural communication teaching embedded in English speaking classes. Specifically, this paper studied the first-year-students studying speaking in English Department of Universitas Negeri Semarang and lecturers lecturing speaking lesson in the same university. The study design, method, and approach implemented in this study, respectively, were case study, qualitative, and interdisciplinary. In addition, data were collected through observation, interview, and documentation study, and were validated by using triangulation technique. The collected data were analyzed using interactive model, comprising data reduction, data presentation, and verification. Results showed that the knowledge of culture, both native and foreign one, was embedded in teaching speaking classes of first-year-students in Universitas Negeri Semarang. The local culture itself served as benchmark and departing point of teaching intercultural communication to students. By acting as a benchmark, local culture gave students a standard of what considered acceptable and not acceptable both in native and foreign culture. While as a departing point, local culture served as the initial knowledge of students before getting to understand the concept of international communication further. For teaching speaking in general, local culture which was used as a ground to introduce intercultural communication would be beneficial for teachers to teach polite oral English communication which was acceptable for speakers coming from various nations.